PENERAPAN MODEL PEMBELAJARAN SAVI BERMUATAN PETA PIKIRAN UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPA SISWA KELAS V SD - I Gede Astawan; Dewa Nyoman Sudana (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: The classroom action research was intended to describe (1) the improvement of the learning motivation, (2) the natural science learning outcome, and (3) the students ’ respond on the implementation of SAVI teaching and learning model by utilizing mind map. The subjects of the study were the fifth graders of Public Elementary School 08 West Tianyar. The data was collected from observation, questionnaire, and test. The results of the study suggested that (1) the implementation of the SAVI teaching and learning model could improve the learning motivation of the students (15.84%); (2) the implementation of the SAVI teaching and learning model could improve the natural science learning outcome of the students (13.49%); (4) the students’ to the implementation of the SAVI teaching and learning model by utilizing mind map was very positive and it was enjoyable.Keywords: learning motivation, learning outcome, SAVI teaching and learning, mind mapAbstrak: penelitian ini tindakan kelas ini bertujuan mendeskripsikan (1) peningkatkan motivasi belajar, (2) peningkatkan hasil belajar IPA, dan (3) tanggapan siswa tentang penerapan model pembelajaran SAVI bermuatan peta pikiran. Subjek penelitian adalah siswa kelas V SD No. 8 Tianyar Barat. Data dikumpulkan melalui observasi, kuesioner, tes, dan angket. Hasil penelitian menunjukkan (1) penerapan model pembelajaran SAVI dapat meningkatkan motivasi belajar siswa (15,84%); (2) penerapan model pembelajaran SAVI dapat meningkatkan hasil belajar IPA siswa (13,49%); (3) tanggapan siswa terhadap penerapan model pembelajaran SAVI berbantuan peta pikiran “sangat positif” dan menyenangkan.Kata-kata kunci: motivasi belajar, hasil belajar, pembelajaran SAVI, peta pikiran.